2011
DOI: 10.1007/s11027-011-9282-1
|View full text |Cite
|
Sign up to set email alerts
|

Health officials’ perceptions of and preparedness for the impacts of climate variability on human health in the Somali region of Ethiopia

Abstract: Perception, Preparedness, Health professionals, Climate variability, Flood,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 7 publications
1
12
2
Order By: Relevance
“…This study found that while slightly more than half (52.3%) of the students stated that climate change could have an impact on human health the remaining students either did not make this association or were uncertain. This finding differs from a study in the Somali Region of Ethiopia, where 80.1% of the local health officials were aware of the role of climate change in human health [ 19 ]. These differences may be due to the fact that Somali Region is highly prone to climate change and climate variability [ 30 ], where health officials may thus be highly aware of this problem.…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…This study found that while slightly more than half (52.3%) of the students stated that climate change could have an impact on human health the remaining students either did not make this association or were uncertain. This finding differs from a study in the Somali Region of Ethiopia, where 80.1% of the local health officials were aware of the role of climate change in human health [ 19 ]. These differences may be due to the fact that Somali Region is highly prone to climate change and climate variability [ 30 ], where health officials may thus be highly aware of this problem.…”
Section: Discussioncontrasting
confidence: 95%
“…This finding differs from a study in the Somali Region of Ethiopia, where 80.1% of the local health officials were aware of the role of climate change in human health [19]. These differences may be due to the fact that Somali Region is highly prone to climate change and climate variability [30], where health officials may thus be highly aware of this problem.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…In recent decades, countless studies have demonstrated the indisputable fact of climate change (IPCC, 2013) and its impacts on water resources (Raghavan et al, 2012;Deng et al, 2015;Pumo et al, 2016), ecological environment (Chen et al, 2013;Yang et al, 2015), human settlement (Dumenu and Obeng, 2016), and human health (Wu et al, 2016;Moore et al, 2008;Abaya et al, 2011). Continued global climate change in desert regions of the world may have a profound impact by accelerating hydrological processes and increasing the unpredictability of related hydrometeorological variables (Gan, 2000;Ma et al, 2004;Jentsch and Beierkuhnlein, 2008), leading to a re-shaping of desert-dryness patterns.…”
Section: Introductionmentioning
confidence: 99%